Comparing health care workforce in circumpolar regions: patterns, trends and challenges ... - Young, T. Kue; Fedkina, Natalia; Chatwood, Susan; Bjerregaard, Peter (University of Alberta Library, 2018)
"The eight Arctic States exhibit substantial health disparities between their remote northernmost regions and the rest of the country. This study reports on the trends and patterns in the supply and distribution of physicians, dentists and nurses in these 8 countries and 25 regions and addresses issues of comparability, data gaps and policy implications. We accessed publicly available databases and performed three types of comparisons: (1) among the 8 Arctic States; (2) within each Arctic State, between the northern regions and the rest of the country; (3) among the 25 northern regions. The unit of comparison was density of health workers per 100,000 inhabitants, and the means of three 5-year periods from 2000 to 2014 were computed." (as cited in abstract) ...